PENGARUH PELATIHAN, KEPERCAYAAN DIRI DAN KETERAMPILAN DALAM BERKOMUNIKASI TERHADAP PADA KEMAMPUAN PUBLIC SPEAKING PADA MAHASISWA STIE TAMANSISWA BANJARNEGARA TAHUN 2024 - Lustono, Lustono; Lusaputra, Fadhil Ghani; Hayati, Sri (Sekolah Tinggi Ilmu Ekonomi Tamansiswa Banjarnegara, 2024)
ABSTRACT This study aims to analyze whether there is an influence of Training, self-confidence, skills. Communication on Public Speaking Ability This study uses multiple regression analysis tools by first converting the ordinal scale to an interval scale through the method of successive intervals. The classical assumption used in this study is the normality test aims to test whether in the regression model the dependent variable and the independent variable both have a normal distribution or not. A good regression model is one that has a normal or near-normal data distribution. The assumption of multicollinearity is a situation where there is a correlation between independent variables between one and another. Heteroscedasticity is cross-section data containing a heteroscedastic situation because the data collects data that represents various sizes. This study uses primary data Primary data is obtained directly by distributing questionnaires to respondents. Respondents in this study were 100 students. The results of the study include: Training has a significant effect on the Public Speaking Ability of STIE Tamansiswa Banjarnegara students. The results of the study include: Self-confidence has a significant effect on the Public Speaking Ability of STIE Tamansiswa Banjarnegara students., Communication skills have a significant effect on the Public Speaking Ability of STIE Tamansiswa Banjarnegara students. Training, Self-confidence, and Communication skills have a significant effect on the Public Speaking Ability of STIE Tamansiswa Banjarnegara students.